On Ronald Langacker’s Semanticocentrism (Revista de Estudos da Linguagem, 2024)
Ray Jackendoff understands that Noam Chomsky’s linguistic models distort the nature of language due to its ‘syntactocentrism.’ Coined by Jackendoff, this term means Chomsky’s assumption that the syntactic component of language is central while the phonological and semantic components are merely interpretive. Jackendoff also states that since the 1970s many researchers have made a mistake opposite to Chomsky’s, by denying that syntax has a relevant role in grammar. Considering such a scenario, this paper analyzes Ronald Langacker’s cognitive grammar, in which syntax is replaced by semantics as the central linguistic component. The goal is to show how Langacker misrepresented language structure by doing so.